Postmortem acinar autolysis in rat sublingual gland: a morphometric study (Journal of Applied Oral Science, 2010)
ABSTRACT OBJECTIVE: To analyze and to quantify morphological acinar postmortem changes in rat sublingual glands (SLG). MATERIAL AND METHODSs: Fifty rats were divided into two groups of 25 animals each. Group I was used for morphological and morphometric evaluations and group II for the determination of gland density and processed gland volume. Acinar autolytic changes were studied at 0 (control group), 3, 6, 12 and 24 h postmortem periods. The morphometric analysis of the volume density (Vv) and total volume (Vt) of intact (ia) and autolyzed (aa) acini was performed under light microscopy using a Zeiss II integration grid with 100 symmetrically distributed points. RESULTS: Morphologically, temporal progressive nuclear alterations and gradual loss of the structural architecture of acinar cells were found. Regarding quantitative results, both the Vvaa and the Vvia showed statistically significant differences among all postmortem periods (p